2005
DOI: 10.1039/b417134a
|View full text |Cite
|
Sign up to set email alerts
|

A quarter of a century of explorations in organozirconium chemistry

Abstract: Systematic explorations of organozirconium chemistry over the past quarter of a century have led to the discoveries and development as well as structural and mechanistic clarifications of novel Zr-catalyzed and -promoted carbon-carbon bond-forming reactions including (i) Ni- or Pd-catalyzed cross-coupling reaction of organozirconiums, (ii) Zr-catalyzed carboalumination of alkynes, (iii) Zr-catalyzed asymmetric carboalumination of alkenes, (iv) generation and carbometallative ring expansion of zirconacyclopropa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(66 citation statements)
references
References 209 publications
2
63
0
1
Order By: Relevance
“…As shown, the substrate bearing a trimethylsilyl (TMS)-and t-butyldimethylsilyl (TBDMS or TBS)-substituent undergoes cyclization/aldehyde addition to deliver a product where C-C bond formation has occurred at the site a-to the TMS group (in preference to the TBDMS group). 4 or ClTi(Oi-Pr) 3 (1 equivalent) Although the yield for the product was reported to be only 41% (half of that observed for other examples), and a precise selectivity was not given for this process, the authors report that the other possible regioisomer 'could not be isolated. ' In related studies targeting intermolecular functionalization of metallacyclopentadienes generated from Ti-mediated diyne cyclization, it has been demonstrated that site-selective allylation is possible (Scheme 5B).…”
Section: Development Of New Ti-mediated Cyclization/functionalizationmentioning
confidence: 86%
See 3 more Smart Citations
“…As shown, the substrate bearing a trimethylsilyl (TMS)-and t-butyldimethylsilyl (TBDMS or TBS)-substituent undergoes cyclization/aldehyde addition to deliver a product where C-C bond formation has occurred at the site a-to the TMS group (in preference to the TBDMS group). 4 or ClTi(Oi-Pr) 3 (1 equivalent) Although the yield for the product was reported to be only 41% (half of that observed for other examples), and a precise selectivity was not given for this process, the authors report that the other possible regioisomer 'could not be isolated. ' In related studies targeting intermolecular functionalization of metallacyclopentadienes generated from Ti-mediated diyne cyclization, it has been demonstrated that site-selective allylation is possible (Scheme 5B).…”
Section: Development Of New Ti-mediated Cyclization/functionalizationmentioning
confidence: 86%
“…The air-stable precatalyst Cp 2 TiCl 2 has been shown to be competent in cyclization chemistry. Here, cyclization of enynes to bicyclic iminocyclopentenes proceeds with 10 mol% of 'finely ground' Cp 2 TiCl 2 , 20 mol% n-BuLi, and 115 mol% Et 3 2. Although previous attempts to accomplish CO insertion into intermediate titanacyclopentenes derived from enyne cyclization with Cp 2 TiCl 2 /2EtMgBr in tetrahydrofuran (THF) met with failure, 28,37,38 it has been found that the commercially available precatalyst Cp 2 Ti(CO) 2 can be employed to catalyze cyclization and carbonylation to deliver bicyclic cyclopentenones (5 -20 mol% Cp 2 Ti(CO) 2 , 18 psig CO, PhMe, 90 1C).…”
Section: Catalysis In Metallocene-promoted Enyne Cyclizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Zirconocene complexes have been widely employed as reagents for the modification and elaboration of alkenes [1,2]. There are many examples of both stoichiometric and catalytic reactions in which zirconocene dichloride acts as a precursor in the formation of reduced zirconium intermediates that carbometallate or couple alkenes [3][4][5].…”
Section: Introductionmentioning
confidence: 99%